INVESTIGATING THE DIFFICULTIES ENCOUNTERED BY STUDENTS IN PRACTICING SPEAKING IN ENGLISH CLASS" : A Case Study at a Senior High School in South Tangerang, Banten - Juhana, - (2011)
The study aims to find out students' difficulties in speaking English, the causes of and solutions for the difficulties in one senior high school in Tangerang, Banten. This study employed a qualitative research design, implementing characteristics of a case study. The data were obtained through classroom observations, questionnaires and interviews. In terms of findings, the study revealed that students' difficulties in speaking English were caused by both psychological and linguistic factors. The psychological factors include fear of making mistake, shyness, anxiety, lack of confidence and lack of motivation. With regard to the linguistic factors, aspects like lack of vocabulary, lack of understanding of grammatical pattern and incorrect pronunciation have also been sources of students' difficulties in speaking English. This finding suggests that the teachers should be more aware of their students' difficulty to speak in English class. This also indicates that it is important for teachers to understand well their students psychologically and at the same time make an attempt to find a better way of teaching that encourages the students to speak in English class. All these may also reflect the urgency for teachers to teach explicitly important aspects of speaking in the future to overcome the problems or difficulties encountered by the students in speaking English so that they have a better command in speaking English.